CALCULATION AND DESIGN OF CELLULAR CARRYING LAYERS OF AIRFIELD RUNWAY PAVEMENTS - G. M. Murtazaliev; M. M. Batdalov; A. I. Akayev; A. I. Bulgakov; M. M. Payzulaev (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Objectives. The need to ensure the reliable functioning of expensive airfield structures poses great challenges for surveyors, designers, builders and operators of these structures. These tasks are complicated by the continuous development of aircraft, an increase in the intensity of their movement, an increase in mass, take-off and landing characteristics of aircraft and the degree of operational impact of aircraft on airfield structures. The aim of the study is the technological solution model proposed by the authors for the carrier layer of artificial runway pavement in the form of a honeycomb structure of closed steel sheets filled with concrete along with a method for assessing the strength and determining the rigidity of its aggregate.Method. A method is proposed for assessing the ultimate strength and determining the real stiffness parameters of structural layers of a runway with a constructive solution to the question of concrete work in cramped conditions (“cage effect”) from the impact of manifold repeated operational aircraft loads. This method is based on the fundamental principles of the deformation theory of reinforced concrete, developed by V.M. Bondarenko and elaborated in relation to the volumetric stress state of reinforced concrete structures in the works by G.A. Geniev, K.L. Surov and V.I. Rimshin.Result. An analytical dependency is obtained for establishing a discrete value, a generalised (integral) parameter of the material deformation of the carrier layer, i.e. the equation of the mechanical state of steel-reinforced concrete in a complex stress state, as well as the repeated application of an operational aircraft load at an arbitrary stress point of the artificial runway pavement taking into account the influence of changes in strength, reinforcement, temperature, humidity and rheological factors.Conclusion. The introduction of new technological principles for reinforcing and concrete laying into the design solutions of the bearing layers of artificial runway pavement allows their bearing capacity and rigidity to be significantly increased due to the redistribution of impact energy and the efficient use of the properties of structural materials during loading.